GWAS of epigenetic aging rates in blood reveals a critical role for TERT - Ake T. Lu (Nature Portfolio, 2018)
Epigenetic clocks based on DNA methylation levels are estimators of chronological age. Here, the authors perform a GWAS of epigenetic aging rates in blood and find SNP variants in the TERT locus associated with increased intrinsic epigenetic age are also associated with longer telomeres.